HASIL DAN MUTU JAGUNG MANIS (ZEA MAYS SACCHARATA STURT) DENGAN PERLAKUAN PUPUK KANDANG AYAM DAN KALIUM - N, Muhammad Yusuf (Agrium, 2018)
The aim of this research was to know the effect of chicken manure and potassium on the yield and quality of sweet corn. The research used a Randomized Block Design Factorial with 2 factors and 3 replications. The first factor is chicken manure: A0 (0 Kg/ha), A1 (10 Kg/ha), A2 (15 Kg/ha) and A3 (20 Kg/ha). The second one is potassium fertilizer: K0 (0 Kg K2O/ha), K1 (90 Kg K2O/ha),K2 (120 Kg K2O/ha), and K3 (150 Kg K2O/ha). The result research showed a not significant increased in the yield and quality of sweet corn. The combination of treatment A0K2 gave the best yield and quality.